2018
DOI: 10.1186/s13012-018-0717-x
|View full text |Cite|
|
Sign up to set email alerts
|

Engaging policy-makers, health system managers, and policy analysts in the knowledge synthesis process: a scoping review

Abstract: BackgroundIt is unclear how to engage a wide range of knowledge users in research. We aimed to map the evidence on engaging knowledge users with an emphasis on policy-makers, health system managers, and policy analysts in the knowledge synthesis process through a scoping review.MethodsWe used the Joanna Briggs Institute guidance for scoping reviews. Nine electronic databases (e.g., MEDLINE), two grey literature sources (e.g., OpenSIGLE), and reference lists of relevant systematic reviews were searched from 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 59 publications
0
87
0
2
Order By: Relevance
“…Co-creation has become more widely used as it allows an alignment of research and intervention development to better address the needs of the targeted populations. 41 A recent scoping review found that co-creation approaches are gaining traction in implementation research 49. However, this study did not include communities or possible users and highlighted the need to test this approach to developing interventions.…”
Section: Lessons Learnedmentioning
confidence: 97%
“…Co-creation has become more widely used as it allows an alignment of research and intervention development to better address the needs of the targeted populations. 41 A recent scoping review found that co-creation approaches are gaining traction in implementation research 49. However, this study did not include communities or possible users and highlighted the need to test this approach to developing interventions.…”
Section: Lessons Learnedmentioning
confidence: 97%
“…Our study included three activities and used methods that are frequently used to elicit feedback from KUs [8].…”
Section: Discussionmentioning
confidence: 99%
“…In knowledge synthesis studies, KUs are primarily engaged as key informants and methods for engaging them in review [8,21,22]. In addition, KUs are mainly used for only one step of the research process; specifically, of 91 studies on KU engagement in knowledge synthesis studies, only 11% (n 5 10) used KUs in at least three steps [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While research in patient engagement has focused on patient input in developing research priorities [24] and core outcome sets [25] for inclusion in primary research, there is also a need to engage patients in the conduct of systematic reviews. A recent scoping review identified that KUs are frequently engaged as key informants in meetings, workshops, or participate in surveys and focus groups in the knowledge synthesis process [26]. Engaging KUs such as patients, clinicians, and policymakers in systematic reviews can have several benefits, such as improving review relevance and quality as well as increasing dissemination and uptake of findings [27].…”
Section: Discussionmentioning
confidence: 99%